Impact of First-Line Antimicrobials on Chlamydia trachomatis-Induced Changes in Host Metabolism and Cytokine Production - Käding, Nadja; Schmidt, Nis; Scholz, Celeste; Graspeuntner, Simon; Rupp, Jan; Shima, Kensuke (Frontiers in Microbiology, 2021)
Urogenital infections with Chlamydia trachomatis (C. trachomatis) are the most common bacterial sexually transmitted diseases worldwide. As an obligate intracellular bacterium, chlamydial replication and pathogenesis depends on the host metabolic activity. First-line antimicrobials such as doxycycline (DOX) and azithromycin (AZM) have been recommended for the treatment of C. trachomatis infection. However, accumulating evidence suggests that treatment with AZM causes higher rates of treatment failure than DOX. Here we show that an inferior efficacy of AZM compared to DOX is associated with the metabolic status of host cells. Chlamydial metabolism and infectious progeny of C. trachomatis were suppressed by therapeutic relevant serum concentrations of DOX or AZM. However, treatment with AZM could not suppress host cell metabolic pathways, such as glycolysis and mitochondrial oxidative phosphorylation, which are manipulated by C. trachomatis. The host cell metabolic activity was associated with a significant reactivation of C. trachomatis after removal of AZM treatment, but not after DOX treatment. Furthermore, AZM insufficiently attenuated interleukin (IL)-8 expression upon C. trachomatis infection and higher concentrations of AZM above therapeutic serum concentration were required for effective suppression of IL-8. Our data highlight that AZM is not as efficient as DOX to revert host metabolism in C. trachomatis infection. Furthermore, insufficient treatment with AZM failed to inhibit chlamydial reactivation as well as C. trachomatis induced cytokine responses. Its functional relevance and the impact on disease progression has to be further elucidated in vivo.